Side-stepped by the green revolution: farmers` traditional rice cultivars in the uplands and rainfed lowlands - Fujisaka, Sam (Intermediate Technology Publications (ITP), 1999)
SINCE THE mid-1960s, rice farmers in the irrigated areas of Asia have rapidly adopted `Green Revolution` rices because of their responsiveness to nitrogen fertilizer and their higher yields, shorter crop duration, and shorter stature. Such cultivars were well suited to systems with good water control and moderate to high management inputs. Although modern rice cultivars have been adopted in less favourable environments, farmers also continue to rely on their traditional cultivars in the uplands and rainfed lowlands. Rice breeding strategies are now being developed that are more tailored to such unfavourable rice environments. Farmers` criteria for selecting or rejecting different rices in the unfavourable regions constitute a valuable resource for programmes interested in improving the productivity of such bypassed areas.